2009
DOI: 10.1007/s12272-009-1802-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein tyrosine nitration in neurodegenerative diseases and atherosclerosis

Abstract: Nitric oxide generates reactive nitrosative species, such as peroxynitrite (ONOO(-)) that may be involved in a number of diseases. ONOO(-) can mediate protein tyrosine nitration which causes structural changes of affected proteins and leads to their inactivation. Various proteomics and immunological methods including mass spectrometry combined with both liquid and 2-D PAGE, and immunodetection have been employed to identify and characterize nitrated proteins from pathological samples. This review presents the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 75 publications
0
50
0
3
Order By: Relevance
“…In contrast to this, ATF3 strongly inhibited GCK nitration in ethanol-cotreated cells (lane 6), despite the fact that ethanol-induced iNOS expression did not change by ATF3, which may be due to the almost complete reduction of GCK protein expression by ethanol and ATF3 combination. Previous studies have demonstrated that protein nitration may cause a functional loss of many proteins through inhibition of critical Tyr residues on the nitrated proteins (47). GCK activity to convert glucose to glucose-6-phosphate was also inhibited by ethanol or SIN-1, which was reversibly restored by L-NMMA, UA, and deferoxamine (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…In contrast to this, ATF3 strongly inhibited GCK nitration in ethanol-cotreated cells (lane 6), despite the fact that ethanol-induced iNOS expression did not change by ATF3, which may be due to the almost complete reduction of GCK protein expression by ethanol and ATF3 combination. Previous studies have demonstrated that protein nitration may cause a functional loss of many proteins through inhibition of critical Tyr residues on the nitrated proteins (47). GCK activity to convert glucose to glucose-6-phosphate was also inhibited by ethanol or SIN-1, which was reversibly restored by L-NMMA, UA, and deferoxamine (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…[1][2][3] Recently, the novel nitrosative modification on tyrosine residues, which is the introduction of a nitroso group (-NO) on tyrosine residues by peroxynitrite and tetranitromethane (TNM), has been reported. 4 Protein tyrosine nitration exhibits a certain degree of selectivity, as not all tyrosine residues of proteins are the substrates for nitration.…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide (NO), an important multifunctional biomolecule, exerts various cytotoxic effects including inhibition of mitochondrial function and activation of endoplasmic reticulum stress [14], and is known to be involved in a variety of diseases such as neurodegenerative disorders, arteriosclerosis, and diabetes mellitus [13,20]. For instance, endoplasmic reticulum stress triggered by NO overproduction, leads to b-cell apoptosis via CHOP induction and caspase-12 activation [29].…”
Section: Introductionmentioning
confidence: 99%